Reading Patterns, Scanning, and the “Control F”/Search Icon: How Students Really (Don’t) Read - Dakakni , Deema; Safa , Nehme (International Research in Education, 2023)
The purpose of this research was to investigate whether digital reading had an impact on reading skills, as well as students’ tendencies to read online or offline in the L2 English speaking classroom. This quantitative-qualitative mixed methods case study involved was comprised of a convenient, purposive sample of 15 participants for semi structured focus group interviews in an English-speaking private university. The findings seem to suggest that reading digitally prods students not only to adopt skimming patterns, but to use the “Control F” command to bypass reading altogether. Furthermore, students’ reading preferences for online/offline material was also revealed, showing a significant tendency of students to revert to online material “just to understand” or “get an idea” while deep understanding was substantially associated with preference for offline reading.